MODEL PEMBELAJARAN DISKUSI KELOMPOK BERNOMOR DALAM PEMBELAJARAN MEMBACA PEMAHAMAN ARTIKEL - Dingding Haerudin (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2010)
This study aims to describe the reading ability and the effectiveness of the Numbered Group Discussion (NGD) learning model in an attempt to improve the article reading ability. It was an experimental study. The data were collected through tests, observations, questionnaires, and interviews. The participants were students of Jurusan Pen¬di¬dikan Bahasa Daerah FPBS UPI. The findings show that the NGD learning model was capable of improving the learning achievement. The students ofthe experimental group learning through the NGD model had an improvement of 3.70 and those of the control group had an improvement of 1.21. In terns of the mastery level, the experimental group improved from the poor category to the moderate category, while the control group was in the poor category. In the literal, inferential, and evaluation aspects, the experimental group showed an improvement from the pretest to the posttest. In relation to the learning process quality, the NGD model can be an effective method for both the students and lecturers.